Product Lifecycle Management - Grieves Michael (MC Graw Hill, 2005)
Product Lifecycle Management (PLM) is the newest wave in productivity. This revolutionary approach is an outcome of lean thinking; however, PLM eliminates waste and efficiency across all aspects of a product's life--from design to deployment--not just in its manufacture. By using people, product information, processes, and technology to reduce wasted time, energy, and material across an organization and into the supply chain, PLM drives the next generation of lean thinking.